2020
DOI: 10.1590/2358-2936e2020023
|View full text |Cite
|
Sign up to set email alerts
|

Histology of the hepatopancreas and anterior intestine in the freshwater prawn Macrobrachium carcinus (Crustacea, Decapoda)

Abstract: The purpose of this study was to describe the structure of the midgut (hepatopancreas and intestine) in the endemic species, Macrobrachium carcinus. Thirty specimens were collected, and the midgut was fixed in Bouin's solution for histological and histochemical analyzes by light microscopy. The hepatopancreas consists of two lobes that connect to the end of the stomach by primary ducts, which originate secondary tubules or hepatopancreatic ducts, that branch into hepatopancreatic tubules. The hepatopancreatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 52 publications
(93 reference statements)
0
13
0
Order By: Relevance
“…According to Hidir et al [38], the accumulation of B-cells during the late stage of ovarian maturation is closely related to the secretion of the digestive enzymes in the mud crabs, S. olivacea. The final product of this intracellular digestion will be further assimilated by the R-cells for metabolism and energy storage, either in the form of lipid or glycogen [60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…According to Hidir et al [38], the accumulation of B-cells during the late stage of ovarian maturation is closely related to the secretion of the digestive enzymes in the mud crabs, S. olivacea. The final product of this intracellular digestion will be further assimilated by the R-cells for metabolism and energy storage, either in the form of lipid or glycogen [60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…When examining the growth promotion effects of probiotics, gut physiology could not be neglected. The digestive tract of decapod crustaceans can be arbitrarily divided into three parts, namely the foregut, midgut, and hindgut [427,428] . Histological studies revealed that significant morphological changes typically occur in the midgut region of shrimps following probiotic administration [162] .…”
Section: Modifying the Gastrointestinal Morphologymentioning
confidence: 99%
“…It is relatively large and typically constitutes 2 to 6% of the total body weight of a decapod [428] . The hepatopancreas is a versatile organ that plays essential roles in the digestive system through the regulation of numerous processes such as steroid hormone synthesis, digestive enzymes secretion, carbohydrate and lipid metabolism, nutrient absorption, storage, and distribution [427][428][429][430][431][432] . Besides, the hepatopancreas also acts as the main detoxification organ for shrimps, particularly during the rapid growth phase [432] .…”
Section: Hepatopancreasmentioning
confidence: 99%
See 2 more Smart Citations